Comparative efficacy of different modules on pulmonary functions after lung resection - Gandhi, Sanjay; Kumar, G. V. R. (International Surgery Journal, 2017)
Background: Lung resection in patients with lung cancer and inflammatory lung pathology, not only improves the symptoms but also long-term survival. The aim of this study was to compare the effect of conventional chest physiotherapy, continuous positive airway pressure (CPAP) and incentive spirometry (IS) after lung resection on pulmonary function tests and postoperative pulmonary complications. Methods: A prospective, randomized, case control study was conducted in a tertiary care teaching hospital. Thirty patients were included, who underwent lung resection. Detailed clinical history, examination and appropriate investigations were done. Patients were randomized into three groups, and accordingly postoperative incentive spirometry with physiotherapy, CPAP with physiotherapy and physiotherapy alone was given. All the groups were compared pre-and postoperatively for pulmonary functions and complications. Results: Majority males (90%) patients of 40-60 years. Significant difference was present in FEV1/FVC on post-OP day one and day twenty-eight only (p<0.05). FVC in all three groups declined most significantly on first postoperative day and then consistently increased till 28th day. Group II and III patients showed a significant difference in increase in FVC between 8th and 28th postoperative day. In group, I maximum increase in FEV1 occurred till day 8th, whereas in group II and III significant difference was still present on day 28th. There was no significant difference between the three groups with regard to FVC, FEV1 and FEV1/FVC. No significant difference in pH value while pO2 showed a marked decrease on first post-op day in all groups. Incidence of atelectasis was found to be highest in group I (5 out of 11). Conclusions: As incentive spirometry offered no advantage over chest physiotherapy but does involve the added expense of spirometer, a vigorous chest physiotherapy requires no special equipment and can be delivered by less trained personnel, chest physiotherapy is more economic.